Sistem Pakan Cerdas Berbasis IoT Untuk Optimalisasi Peternakan Kambing Umbaran di Era Digital Farm - Zahrowani, Rizal; Kuswanto, Jeki; Pramono, Eko (Jurnal Buana Informatika, 2025)
This research aims to create a smart feeding system based on the Internet of Things (IoT) to enhance the efficiency of feed delivery in goat farming. The system automatically regulates the feed dispenser according to a predetermined schedule, making it easier for farmers to manage feed. System testing demonstrates its effectiveness in reducing feed delivery time and minimizing waste. The system features an LCD screen that displays the dispenser status, providing real-time information to farmers. This technology also allows for remote monitoring, enabling farmers to manage feed more effectively. The implementation of this system is expected to improve productivity and animal welfare while promoting modernization in farming practices in Indonesia. This innovation is anticipated to offer a sustainable solution to challenges in feed management, providing long-term benefits for farmers and the livestock industry.